"The Goodest of Functions": The Restoration of Temporality in the Analysis of a Psychotic Child. Issue 1 (1st January 2019) - Meisel, Frederick L.
ABSTRACT: This paper presents the psychoanalysis of a hospitalized psychotic child that validates some current theoretical understanding about primitive, unrepresented states of mind. It highlights the function of fusion as a symbiotic defense against deadness, following the attack on linkage that destroys temporality. It also demonstrates the facility of the transference in play mode to promote internalization in a child walled off from human contact, and then follows the growth and development that ensued.